Private Finance : Are Private Loans and Charitable Giving Replacing Aid? - Harford, Tim; Hadjimichael, Bita; Klein, Michael (World Bank, Washington, DC, 2012)
Private financial flows to developing countries, such as debt,equity, remittances, and private charitable giving, have increaseddramatically over the past 20 years. One commentator has eventrumpeted the privatization of foreign aid. Since privatecharitable giving remains small and developing country governmentsare borrowing more, not less, from official sources, this claim ismisleading. But unprecedented sums are indeed flowing to theprivate sector in developing countries.